Perencanaan Keuangan untuk Mencapai Tujuan Finansial - Sundjaja, Arta Moro (ComTech: Computer, Mathematics and Engineering Applications, 2010)
Financial planning of individuals started a trend in Indonesia in recent years. This paper will attempt to design an individual financial planning. Object of this project include individual financial planning and financial management, investment planning, financial planning elements, prepare an emergency fund and retirement funds, education costs and achieve other financial goals. Of this paper is expected to increase the knowledge of individuals in managing finances and choosing the right media investments and achieve their financial goals.